Seasonal variations of harpacticoid copepod and size-fractionated abundances in relation to environmental changes in Setiu Wetland - Kamaruzama, N. F. S.; Kassim, Zaleha; Jasmani, Safiah; Mohtar, Nor Fazliyana (Triveni Enterprises, 2018)
Aim: Harpaticoid copepods, an important component of fauna in marine environment, play a vital role in aquatic food webs as a source of food for other member of benthic community and the juveniles of predator fish species. Recent data on benthic plankton and nekton composition in coastal wetland of Setiu are useful and important in understanding the interaction between these organisms at different seasons. This maintains the diversity of fish in Setiu Wetland which is a major factor in developing the Wetland as a place for ecotourism and recreational fishing activity. The effort will directly or indirectly benefit the fisheries community living within the wetland which depends on the fisheries sector.